2023
DOI: 10.15252/msb.202211392
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor expression is the main determinant of variability in gene co‐activity

Abstract: Many genes are co-expressed and form genomic domains of coordinated gene activity. However, the regulatory determinants of domain co-activity remain unclear. Here, we leverage human individual variation in gene expression to characterize the co-regulatory processes underlying domain co-activity and systematically quantify their effect sizes. We employ transcriptional decomposition to extract from RNA expression data an expression component related to co-activity revealed by genomic positioning. This strategy r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This observation is also consistent with the notion that cmQTLs frequently disrupt the binding sites of cell-type specific TFs, which then could affect histone modification deposition and cooperation between CREs within a CM in a cell type-specific manner. This finding complements recent observations showing that genetic variants impact CRE interactions relevant for establishing gene expression through direct perturbation of TF binding to enhancers [ 85 ] and that TFs are the main drivers of gene expression cooperativity [ 86 ].…”
Section: Discussionsupporting
confidence: 87%
“…This observation is also consistent with the notion that cmQTLs frequently disrupt the binding sites of cell-type specific TFs, which then could affect histone modification deposition and cooperation between CREs within a CM in a cell type-specific manner. This finding complements recent observations showing that genetic variants impact CRE interactions relevant for establishing gene expression through direct perturbation of TF binding to enhancers [ 85 ] and that TFs are the main drivers of gene expression cooperativity [ 86 ].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, we observed large differences of DNA-binding characteristic of TF Irp between the C48 strain and the DC3000 strain. The functional diversity of TFs may arise from the large difference in the contents of target genes and TFs, which are regarded as the main determinant of transcriptional regulatory(van Duin, Krautz, Rennie, & Andersson, 2023), although Irp display high homology in these pathovars.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of regulatory mechanisms that act on individual genes can provide context-specific understanding of transcriptional regulation and shed light on the role of dysregulation in disease [26][27][28] . Here, we sought to identify genes that are putative targets of significantly associated SCZ genes in the cell type models.…”
Section: Post-twas Analysis: Identifying Regulatory Network For Scz A...mentioning
confidence: 99%